BIOCHEMICAL, HAEMATOLOGICAL AND HISTOPATHOLOGICAL ASSESSMENT OF TOXIC FFECTS OF MANNIHOT ESCULENTA CRANTZ LEAF AQUEOUS EXTRACT IN RATS. - AWE EMMANUEL O,; KOLAWOLE OYETUNJI T, (International Journal of Pharma and Bio Sciences, 2013)
Mannihot esculenta Crantz (cassava) leaves have been used for therapeutic purposes without considering toxicological effects. This study was designed to evaluate the toxic effects of aqueous extract of leaf of M. esculenta in Wistar rats. Thirty two Wistar rats were distributed into four groups of eight rats each . Groups 2, 3, 4 were administered orally with M. esculenta leaf aqueous extract at 100, 200 and 400 mg kg-1 body weight respectively for 28 days. Group 1 was control and received no treatment. The effect of aqueous extract of M. esculenta on the body weight, liver enzymes (alanine transaminase ALT, alkaline phosphatase ALP, aspartate transaminase AST), total protein, urea and hematological parameters were evaluated. Pathological changes in the liver were also examined. Oral administration of aqueous extract of leaf of M. esculenta resulted in significant increase (P<0.05) in ALT, ALP activities, decrease in body weight and mild to severe histological changes in the liver compared with control. The aqueous extract of leaf of M. esculenta appears to be toxic at the doses tested. The toxic effects observed might be due to the presence of cyanogenic glycosides, a known toxic constituent of M. esculenta.